Natural and synthetic flavonoid derivatives as new potential tyrosinase inhibitors: a systematic review. Issue 36 (23rd June 2021) - Obaid, Rami J.; Mughal, Ehsan Ullah; Naeem, Nafeesa; Sadiq, Amina; Alsantali, Reem I.; Jassas, Rabab S.; Moussa, Ziad; Ahmed, Saleh A.
Abstract : This review revealed that among all the natural and synthetic flavonoids, the inhibitory findings suggest that the flavonol moiety can serve as an effective and a lead structural scaffold for the further development of novel TIs. Abstract : Tyrosinase is a multifunctional glycosylated and copper-containing oxidase that is highly prevalent in plants and animals and plays a pivotal role in catalyzing the two key steps of melanogenesis: tyrosine's hydroxylation to dihydroxyphenylalanine (DOPA), and oxidation of the latter species to dopaquinone. Melanin guards against the destructive effects of ultraviolet radiation which is known to produce considerable pathological disorders such as skin cancer, among others. Moreover, the overproduction of melanin can create aesthetic problems along with serious disorders linked to hyperpigmented spots or patches on skin. Several skin-whitening products which reduce melanogenesis activity and alleviate hyperpigmentation are commercially available. A few of them, particularly those obtained from natural sources and that incorporate a phenolic scaffold, have been exploited in the cosmetic industry. In this context, synthetic tyrosinase inhibitors (TIs) with elevated efficacy and fewer side effects are direly needed in the pharmaceutical and cosmetic industries owing to their protective effect against pigmentation and dermatological disorders. Furthermore, the biological significance of the chromone skeleton and its associated medicinal and bioactive properties has drawn immense interest and inspired many researchers to design and develop novel anti-tyrosinase agents based on the flavonoid core (2-arylchromone). This review article is oriented to provide an insight and a deeper understanding of the tyrosinase inhibitory activity of an array of natural and bioinspired phenolic compounds with special emphasis on flavonoids to demonstrate how the position of ring substituents and their interaction with tyrosinase could be correlated with their effectiveness or lack thereof against inhibiting the enzyme.